Effect of inulin-type fructoligosaccharides (FOS) from yacon on the physicochemical and sensory characteristics of bread - Pérez-Mejía, Giancarlo Joel (2024)
The current food industry drives interest in foods that not only satisfy basic needs, but also promote health. In this context, yacon, with its fructooligosaccharides (FOS)-rich syrup, emerges as a valuable plant source for improving the properties of bread. This study evaluated the effects of FOS addition from yacon on the physicochemical and sensory characteristics of bread. A traditional methodology involving bread making with different concentrations of the syrup was employed. The results revealed that the treatments with 0.5% and 1.5% yacon syrup excelled in bulk density, crumb cell shape and crumb appearance. In the sensory evaluation, the 0% and 0.5% treatments scored best in crust colour, texture and flavour. In conclusion, the addition of FOS to bread was shown to significantly improve its physicochemical and sensory characteristics: the addition of 1.5% and 0.5% improved bread density and appearance, while the 0% and 0.5% treatments obtained better sensory ratings.